Rural Bilingual Roma Children and Theory of Mind Competencies - Kyuchukov, Hristo (Lesya Ukrainka Eastern European National University, 2022)
Two age groups of Roma children (3;6-4;6 years old n = 20 and 4;7- 5;6 n = 20) from rural areas of Bulgaria were tested for understanding the classical Theory of Mind (TOM) task (False-belief) and the correlations with two language tests (Evidentiality and Yes/No Questions) were investigated. Coordinate with that the children were tested by means of the nonverbal Knox Cub Intelligent Test. The Theory of Mind tests and the language tests were conducted in both languages – L1 Romani and Bulgarian as their second language. The children attend kindergarten where they learn Bulgarian, but at home, they speak Romani as L1. All children were tested individually in a separate room by the researcher. A Roma woman member of the community and speaker of the dialect of the children tested them in Romani. All the results were analysed using ANOVA. The results frоm the study show that in the performance of both TOM tasks, the older children understand better the tasks and a high number of them have correct answers. The children performed equally well on the tests in both languages. The differences between Romani as L1 and Bulgarian as a second language are not significant. In the performance of the language tasks Evidentiality and Yes/No Questions there is a statistically significant correlation (p < .05000). There is also a correlation between L1 Romani and Bulgarian in performing the language tasks (p < .340526). However, there is no correlation between the language tasks and the TOM tasks. There are correlations between the variables Evidentiality Task Scores and Yes/No Question Task Scores (.4064); also between Evidentiality Task Scores and Knox’s Cube Nonverbal Intelligent Test Scores (.3969); and between the Yes/No Question Task Scores and Knox’s Cube Nonverbal Intelligent Test Scores (.5073). All correlations are only for the Romani language. The conclusion from the study is that the bilingual Roma children develop the Theory of Mind competencies around the age of 4;6 years old. Their language proficiency level in Romani and Bulgarian is basically equal, however when performing intelligence task the children are much better in their mother tongue. The children understand the Theory of Mind task in both languages in equal measure.
Keywords: Theory of Mind; Roma children; bilingualism; evidentiality; Yes/No questions